Pengaruh Motivasi Belajar dan Frekuensi Latihan Soal Terhadap Prestasi Belajar Hukum Pajak dan Perpajakan Pada Mahasiswa Pendidikan Akuntansi FKIP Universitas Muhammadiyah Surakarta Tahun 2010/2011 - KHASANAH, Yami Karyati Nurul, Dr. Sabar Narimo, MM, M.Pd, Dr. Wafroturrohmah, SE, MM (2016)
Purposes of the research is to know: 1) Effect of learning motivation on achievement of Tax and Taxation Law Learning; 2) effect of Frequency in doing exercises on achievement of Tax and Taxation Law Learning; 3) effects of learning motivation and Frequency of doing exercises on achievement of Tax and Taxation Law Learning. The research is descriptive-quantitative one. Population of the research is all students of Accounting Education Program of 2010/2011 who had attended Tax and Taxation Law course. The population was 189 students and 120 of them were taken as sample by using proportional random sampling with a draw method. Data of the research was obtained from questionnaire and documentation. The questionnaire had been tried previously and its reliability and validity had been tested. The data was analyzed by using multiple linear regression, t-test, F-test, R2 and relative and effective contribution test. Results of regression analysis obtained equation of regression line, namely: Y = 11.634 + 0.758X1 + 0.926X2. Conclusion that can be drawn were: 1) Learning motivation had significant effect on achievement of Tax and Taxation Law learning with tcalculation> ttable of 15.529>1.98 and significance value of <0.05, namely 0.000 and effective contribution of 36.762%; 2) Frequency of doing exercises had significant effect on the learning achievement with tcalculation> ttable of 17.816>1.98 and significance value of <0.05, namely 0.000 and effective contribution of 45.738%; 3) Learning motivation and frequency of doing exercises had simultaneously significant effect on the learning achievement with Fcalculation>Ftable of 275.556>3.07 and significance value of <0.05, namely 0.000. Coefficient determination of 0.825 indicated that effect magnitude of the learning motivation and frequency of doing exercises on the achievement of Tax and Taxation Law learning was 0.825, whereas the remain of 17.5% was affected by variables other than ones of the study.